Quality assessment of water stored in vessels made of different materials - Jiddimani, Soundarya; Tonni, Sanjeev; Vedantam, Giridhar (Journal of Ayurveda (online), 2021)
Introduction: There can be no state of positive health and wellbeing without a good quality of water. Ayurveda explains many techniques for water purification which are easy to use, economical, and can be easily applied with household resources. Methods: Vessels made of brass, copper, stainless steel and earthen pot were used for the purpose. The physicochemical and microbiological qualities of the drinking water were analysed for each water sample collected during an initial time ("0" hr) and after 24 hr. Results: No change in the physical parameters of the water quality is observed in all vessels from initial "0" hr to after 24 hr. Absence of total fungal count is observed in water stored in three vessels, i.e., copper, earthen, and steel vessel from initial "0"hr to after 24 h. The organisms Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella abony are seen to be absent in all the four vessels in which water is stored from initial "0" h to 24 h. Conclusion: The results obtained in this study reveal that the quality of water stored in copper is better than others.